Media encoding in science fiction television: Battlestar Galactica as a site of critical cultural production. - Chow-White, Peter A.; Deveau, Danielle; Adams, Philippa (Media, Culture & Society, 2015)
We examine the television show Battlestar Galactica (BSG) through interviews with creative people working on the show to illustrate the production context of the show and the science fiction (sf) genre. Media scholars suggest sf stories are critical stories about our political systems and our anxieties about new technologies, social change, race, gender, class, and religious conflicts. We investigate constraints and agency in the production of BSG as a site of critical cultural commentary and the politics of racial and gender representation in the series. We find that the creators behind BSG struggle with the moral and political nature of the stories they create, within the constraints of power, social structures, and a neoliberal economy and in doing so actively participate in their own acts of meaning-making in the production process.